Natural and nature based features for environmental enhancement and coastal storm risk management: a case study on Marco Island, Florida, United States - Dabees, Mohamed A.; Fleming, Matthew; Damon, Marc (Frontiers in Built Environment, 2022)
Natural and Nature-Based systems provide an opportunity for adaptive response to Coastal Storm Risk Management and Sea Level Rise. The Tigertail Lagoon / Sand Dollar Island Ecosystem Restoration on Marco Island, Florida, has been designed to maintain and enhance an existing coastal ecosystem that is evolving toward closure. Design of the project considers the evolution of the inlet shoal and barrier island system to provide a nature-based restoration plan that enhances existing habitats and protection from coastal storm risk. Restoration will improve tidal exchange through restoration of the lagoon flow channel. Total wetland area will be increased by relocating the sand spit seaward of its present location to where it was located in approximately 2017. The reconstructed beach berm will provide enhanced resiliency to high frequency weather events. Sediment will be sourced from the existing sand spit and an innovative sand trap that will maintain the lagoon entrance open while providing beneficial re-use for excess sediment accumulating at the end of the spit. Components of the project were analyzed using the Coastal Modeling System (CMS) and XBeach. Enhancing and preserving this barrier island feature and productive ecosystem provides an example of the enhanced coastal resiliency provided by natural and nature-based systems that are adaptable and responsive to sea level rise and ongoing coastal processes.